Clinical Profile and Outcome of Obstetric Patients Requiring Critical Care Support in a Tertiary Care Centre - Pokhrel, Sita; Ghimire, Ram Hari; Ghimire, Ashima; Shrestha, Prajmi; Chaudhary, Amar Nath (Journal of Nobel Medical College, 2020)
Background: The maternal complications during pregnancy pose very serious challenge requiring multispeciality critical care approach. The objective of the study was to analyse clinical profile and outcome of these patients. Studies regarding above will add on existing knowledge that will help in improving patient outcome. Materials and Methods: This was a prospective observational study conducted over a period of 1 year from April 2017 to March 2018 in the department of obstetrics and gynecology of Nobel Medical College, Biratnagar. All the consecutive patients requiring ICU care were enrolled. Results: Among 7820 deliveries, 122 patients (1.56% of total deliveries) required critical care admission. Among them 61(50%) have causes related to obstetrics problems and 61 (50%) have non obstetric problems. Obstretic hemorrgage (24.59%) and hypertensive disorders (11.47%) of pregnancy were common obstetric complications whereas isolated renal failure 18(14.75%), cardiac disease 16 (13.1%), pulmonary disorders 11(9.1%) and sepsis 10 (8.19%) were common non obstetric complications. Maternal mortality rate was 24.59%.Renal failure 9(30%) was the commonest cause of death. Conclusion: Obstetric hemorrhage and hypertensive disorders of pregnancy were the commonest risk factors requiring critical care support. Other risk factors requiring ICU were renal failure, cardiac disease, pulmonary disorders and sepsis.